Cell Cycle Control Mechanisms and Protocols - Humphrey, Tim; Brooks, Gavin (Humana Press, 2005)
Our understanding of the cell cycle and its regulation has significantly increased with recent discoveries of links to DNA repair, growth, cellular metabolism, development, cell death, proliferative disease, cardiovascular diseases, and cancer. In Cell Cycle Control: Mechanisms and Protocols, internationally recognized researchers not only provide overviews of cell cycle regulatory mechanisms, but also set forth their best techniques for studying the eukaryotic cell cycle and its key regulatory molecules in many major research organisms. Described in step-by-step detail, these readily reproducible methods enable fundamental research on well-defined cell cycle regulators-and those more recently defined-in yeasts, bacteria, plants, Drosophila, Xenopus, and mammals. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and cutting-edge, Cell Cycle Control: Mechanisms and Protocols offers all cell researchers an indispensable collection of critical reviews and techniques essential to investigate how normal cells divide and how this is altered in disease
Keywords: Life Sciences; Cell Biology; Life sciences; Cell biology; Zellzyklus; Regulation; Labortechnik; Aufsatzsammlung